2018
DOI: 10.1044/2018_jslhr-l-17-0103
|View full text |Cite
|
Sign up to set email alerts
|

Morphosyntactic Production and Verbal Working Memory: Evidence From Greek Aphasia and Healthy Aging

Abstract: https://doi.org/10.23641/asha.6024428.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(82 citation statements)
references
References 77 publications
10
69
1
2
Order By: Relevance
“…What follows from this idea is that patterns of morphosyntactic production cannot be pathology-specific, meaning that the same or similar patterns should emerge in different neurological conditions. This prediction is largely borne out by the fact that the pattern reported here for MS is similar to the patterns reported for Greek aphasia (Fyndanis et al, 2012;Fyndanis et al, 2018a) and AD in that, in all three neurological conditions, Aspect was found to be more impaired than Agreement and Time Reference. Contrary to our prediction, the RRMS group did not differ significantly from the SPMS group in any of the three morphosyntactic conditions.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…What follows from this idea is that patterns of morphosyntactic production cannot be pathology-specific, meaning that the same or similar patterns should emerge in different neurological conditions. This prediction is largely borne out by the fact that the pattern reported here for MS is similar to the patterns reported for Greek aphasia (Fyndanis et al, 2012;Fyndanis et al, 2018a) and AD in that, in all three neurological conditions, Aspect was found to be more impaired than Agreement and Time Reference. Contrary to our prediction, the RRMS group did not differ significantly from the SPMS group in any of the three morphosyntactic conditions.…”
Section: Discussionsupporting
confidence: 83%
“…That the same pattern emerged not only in AD and aphasia but also in healthy speakers (e.g., Fyndanis et al, 2018a) is consistent with the idea that pathology only exacerbates patterns or trends observed in healthy speakers (e.g., Dick et al, 2001;Miyake et al, 1994). Furthermore, recent studies showed that WM is critically involved in verb-related morphosyntactic production (e.g., Fyndanis et al, 2018a;Kok et al, 2007). Given that MS is characterized by WM limitations (Brochet & Ruet, 2019) among other deficits , we expect individuals with MS to perform worse than healthy controls on tasks tapping into morphosyntactic production.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations